GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 25 Mar 2019, 11:15

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# If |m - 1| = |n + 1|, what is the value of m — n ?

Author Message
TAGS:

### Hide Tags

Senior DS Moderator
Joined: 27 Oct 2017
Posts: 1221
Location: India
GPA: 3.64
WE: Business Development (Energy and Utilities)
If |m - 1| = |n + 1|, what is the value of m — n ?  [#permalink]

### Show Tags

Updated on: 15 Mar 2019, 00:14
00:00

Difficulty:

85% (hard)

Question Stats:

44% (02:15) correct 56% (02:34) wrong based on 39 sessions

### HideShow timer Statistics

If $$|m-1| = |n+1|$$, what is the value of $$m — n$$?

(1) $$mn > 0$$

(2) $$\frac{m}{n}$$$$\neq{-1}$$

GMATbuster's Weekly GMAT Quant Quiz #5 Ques No 10

_________________

Originally posted by gmatbusters on 20 Oct 2018, 10:44.
Last edited by Bunuel on 15 Mar 2019, 00:14, edited 1 time in total.
Renamed the topic and edited the question.
Manager
Joined: 02 Apr 2018
Posts: 50
Re: If |m - 1| = |n + 1|, what is the value of m — n ?  [#permalink]

### Show Tags

20 Oct 2018, 10:52

statement 1 tells us that m and n are either both positive or both negative
lets take the case where theyre both positive:
therefore the absolute value turns into
m-1 = n+1
so m-n = 2

if they're both negative then its
-m+1 = -n-1
and you still get that m-n = 2
Therefore sufficient

Statement 2 rearranged gives you m =! -n
then again you see they have the same signs and it will also be sufficient
Intern
Joined: 08 Feb 2018
Posts: 20
Re: If |m - 1| = |n + 1|, what is the value of m — n ?  [#permalink]

### Show Tags

20 Oct 2018, 11:01
C.

Can't get m-n from first if both are negative. The second is insufficient as it just states that they are same or different sign. Together sufficient.
Intern
Joined: 17 Dec 2016
Posts: 19
Location: Viet Nam
Re: If |m - 1| = |n + 1|, what is the value of m — n ?  [#permalink]

### Show Tags

20 Oct 2018, 11:05

Posted from my mobile device
Attachments

image.jpg [ 1.65 MiB | Viewed 431 times ]

Manager
Joined: 16 Sep 2011
Posts: 97
Re: If |m - 1| = |n + 1|, what is the value of m — n ?  [#permalink]

### Show Tags

20 Oct 2018, 11:11
Given |m-1|=|n+1|

Case 1: which means if m>1 and n>-1
it becomes m-1=n+1
so m-n=2

Case 2: if m<1 and N>-1
1-m=1+n
so, m+n=0

Case 3:if m>1, and n<-1
m-1= -1-n
m+n=0

Case 4:if m<1 and n<-1
1-m=-1-n
so, m-n=2

case 5: m=1 and n=-1
m-1=n+1
which means m-n=2

Option A , mn>0,
which means either m>0, n>0 or m<0 , n<0
if both m, n >0, both case 1 and case 2 are applicable
so not deductible

if both are <0, ie m<0 and n<0
case 3 and case 4 applies
hence A is not sufficinet

Option B: m/n is not equal to -1 which is the limiting case of m=1 and n=-1 or m=-1 and n=1
hence not sufficient

Combing both,
cant decide whether m-n=2 or m+n=0

Re: If |m - 1| = |n + 1|, what is the value of m — n ?   [#permalink] 20 Oct 2018, 11:11
Display posts from previous: Sort by

# If |m - 1| = |n + 1|, what is the value of m — n ?

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne Kindly note that the GMAT® test is a registered trademark of the Graduate Management Admission Council®, and this site has neither been reviewed nor endorsed by GMAC®.